2004
DOI: 10.1161/01.cir.0000138382.57325.5c
|View full text |Cite
|
Sign up to set email alerts
|

Apelin Has In Vivo Inotropic Effects on Normal and Failing Hearts

Abstract: Background-Apelin has been shown ex vivo to be a potent cardiac inotrope. This study was undertaken to evaluate the in vivo effects of apelin on cardiac function in native and ischemic cardiomyopathic rat hearts using a novel combination of a perivascular flow probe and a conductance catheter. Methods and Results-Native rats (n ϭ32) and rats in heart failure 6 weeks after left anterior descending coronary artery ligation (n ϭ22) underwent median sternotomy with placement of a perivascular flow probe around the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
189
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(205 citation statements)
references
References 23 publications
12
189
2
2
Order By: Relevance
“…In the present study, the findings revealed that the levels of apelin were lower in stable angina group than in the control (1.24 (14).…”
Section: Apelin Was First Identified As a Native Ligand Of The Orphansupporting
confidence: 42%
“…In the present study, the findings revealed that the levels of apelin were lower in stable angina group than in the control (1.24 (14).…”
Section: Apelin Was First Identified As a Native Ligand Of The Orphansupporting
confidence: 42%
“…Additionally, the apelinergic system has an important role in cardiac function. In the isolated rat heart, infusion of apelin-16 induces a potent dose-dependent positive inotropic effect, with an EC 50 of 40-125 pM in humans and w33 pM in rats (Szokodi et al 2002), an effect also observed in the failing heart (Berry et al 2004). In mice, administration of apelin increases myocardial contraction while reducing cardiac preload and afterload, without causing hypertrophy (Ashley et al 2005).…”
Section: Cardiovascular Roles Of Apelin/apjmentioning
confidence: 99%
“…Apelin has been shown to exert potent positive inotropic effect on normal and failing myocardium. 25,26 Furthermore, apelin has cardioprotective effects against ischemia and reperfusion injury in rats. 27 Several others adipokines have been identified, but whether these modulate cardiac function is not clear so far.…”
Section: Role Of Adipose Tissue In Cardiac Dysfunction C Look Et Almentioning
confidence: 99%